Maybe we can find Some Common Ground: Indigenous Perspectives, a Music Teacher’s Story - Dillon, Steve (The Australian Journal of Indigenous Education, 2007)
Abstract This paper examines the idea of embedding Indigenous perspectives drawing upon a metaphor for designing an environment that nurtures Indigenous cultural identity and relationships. This paper constitutes a teacher’s personal story of emerging understandings of Indigenous Standpoint Theory and pedagogy, which began with embedding Indigenous perspectives within a tertiary music and sound curriculum. These understandings were developed into “rules of thumb” that have had transferable implications for research that examines community music-making projects in urban Indigenous and cross-cultural communities. These ideas are explored through case studies that examine them in context. Furthermore, the idea of embedding Indigenous perspectives in my own value systems is explored and a growing awareness of the embodied understanding that stems from an open, continuous and critical discourse with Indigenous people. This reveals a relationship of belonging and welcoming interfaced with obligation and a growing knowledge of people, community and country and its effect on my “white understanding” of relationships. This proposal stems from several successful projects where participants have experienced both nurturing of Indigenous knowledge and a productive tension. This does not advocate an argument for positive discrimination but rather seeks to build the idea that interfaces which simultaneously develop embodied understanding alongside Indigenous pride can lead to compelling and unique learning experiences for students, teachers and communities.